Fourier Transforms New Analytical Approaches and FTIR Strategies - Nikolic, Goran (IntechOpen, 2011)
New analytical strategies and techniques are necessary to meet requirements of modern technologies and new materials. In this sense, this book provides a thorough review of current analytical approaches, industrial practices, and strategies in Fourier transform application.